A mouse model reveals the events and underlying regulatory signals during the gonadotrophin-dependent phase of follicle development. (16th October 2020) - Chen, Yingjun; Wang, Xiaodong; Yang, Chan; Liu, Qinghua; Ran, Zaohong; Li, Xiang; He, Changjiu
ABSTRACT: During folliculogenesis, the gonadotrophin (GTH)-dependent phase begins at the small antral follicle stage and ends with Graafian follicles. In this study, pregnant mare's serum GTH was used to induce GTH-dependent folliculogenesis in mice, following which the developmental events that follicles undergo, as well as the underlying regulatory signals, were investigated at both the morphological and transcriptomic level. GTH-dependent folliculogenesis consisted of three phases: preparation, rapid growth and decelerated growth. In the preparation phase, comprising the first 12 h, granulosa cells completed the preparations for proliferation and differentiation, shifted energy metabolism to glycolysis, and reduced protein synthesis and processing. The rapid growth phase lasted from 12 to 24 h; in this phase, granulosa cells completed their proliferation, and follicles acquired the capacity for estradiol secretion and ovulation. Meanwhile, the decelerating growth phase occurred between 24 and 48 h of GTH-dependent folliculogenesis. In this phase, the proliferation and expansion of the follicular antrum were reduced, energy metabolism was shifted to oxidative phosphorylation, and cell migration and lipid metabolism were enhanced in preparation for luteinization. We also revealed the key signaling pathways that regulate GTH-dependent folliculogenesis and elucidated the activation sequence of these pathways. A comparison of our RNA-sequencing data with that reported for humans suggested that the mechanisms involved in mouse and human folliculogenesis are evolutionarily conserved. In this study, we draw a detailed atlas of GTH-dependent folliculogenesis, thereby laying the foundation for further investigation of the regulatory mechanisms underlying this process.